Seasonal rhythm of evolution of curly honeysuckle's introduced in the dendropark Sofiivka of the NAS of Ukraine - G.I. Muzyka (Інтродукція Рослин, 2000)
Peculiarities of seasonal rhythm of evolution of curly honeysuckles introduced in the dendropark Sofiivka are considered. Dependence between the periods of relative rest, correlation of duration of certain rest phases and geographical latitude of natural areas of curly honeysuckles has been determined.